2013
DOI: 10.1590/s0103-18132013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Working memory capacity and L2 speech performance in planned and spontaneous conditions: a correlational analysis

Abstract: The present study is part of a larger scale research that investigates the relationship between working memory capacity, pre-task planning, and L2 speech performance. The aim of the study was to analyze 1) the relationship between working memory capacity and L2 speaking performance in spontaneous conditions and 2) the relationship between working memory capacity and L2 speaking performance in planned conditions. L2 speech performance was analyzed in terms of fluency, accuracy and complexity. Results indicate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Working Memory (WM) can be defined as the capacity to temporarily store a limited amount of information that is available for manipulation by higher-order cognitive processes, such as language comprehension and production (Baddeley, 2012). Research in both first and second language (L2) acquisition has demonstrated that limitations in WM capacity may constrain the processes involved in language acquisition (Daneman & Green, 1986;Fortkamp, 1999;Gathercole & Baddeley, 1993;Guará-Tavares, 2008;Martin & Ellis, 2012). It has been acknowledged that individuals with higher WM capacity experience fewer difficulties than individuals with lower WM capacity in their attempts to learn an L2 successfully because of their increased aptitude to learn (Linck, Osthus, Koeth, & Bunting, 2014).…”
mentioning
confidence: 99%
“…Working Memory (WM) can be defined as the capacity to temporarily store a limited amount of information that is available for manipulation by higher-order cognitive processes, such as language comprehension and production (Baddeley, 2012). Research in both first and second language (L2) acquisition has demonstrated that limitations in WM capacity may constrain the processes involved in language acquisition (Daneman & Green, 1986;Fortkamp, 1999;Gathercole & Baddeley, 1993;Guará-Tavares, 2008;Martin & Ellis, 2012). It has been acknowledged that individuals with higher WM capacity experience fewer difficulties than individuals with lower WM capacity in their attempts to learn an L2 successfully because of their increased aptitude to learn (Linck, Osthus, Koeth, & Bunting, 2014).…”
mentioning
confidence: 99%
“…The cognitive factor investigated in the present study, working memory, has been found to be a robust predictor of second language learning (for recent reviews, see Wen, 2016;Wen et al, 2017;Singleton, 2017), above all in studies on vocabulary and grammar learning (Sanz, Lin, Lado, Stafford & Bowden, 2014). However, few studies (Gilabert & Muñoz, 2010;Guara-Tavarés, 2013;Kormos & Safar, 2008;Kormos, 2012b;Kormos & Trebits, 2011;Mota, 2003;Tagarelli, Ruiz, Moreno & Rebuschat, 2016;Zalbidea, 2017) have examined the relationship between working memory and different dimensions of language performance, namely, complexity (both structural and lexical), accuracy and fluency (henceforth, CAF). Furthermore, these studies have come to mixed results, as will be discussed in more detail below, and they often address only one or two dimensions, with only some studies including the four dimensions of linguistic performance.…”
Section: Background Of the Studymentioning
confidence: 82%
“…On the other hand, attentional resources are limited (among others: Anderson, 1983, Baddeley, 2003Kane & Engle, 2003;Lepsien, Thorntona & Nobrea, 2011;Magimairaj & Montgomery, 2013;Miyake et al, 2000;Paradis, 1993), and different aspects of performance compete for attentional resources (e.g. Guara-Tavarés, 2013;Forthkamp, 1999;Forthkamp & Bergsleithner, 2010;Robinson, 2001;Skehan, 1998). This, for instance, would be the case of the CAF dimensions of linguistic performance investigated in the empirical part of this paper.…”
Section: Background Of the Studymentioning
confidence: 99%
“…One of the objectives of research in the field of Second Language Acquisition (SLA) is to develop pedagogical strategies that may assist learners to evolve as users of an L2, for the purposes they might wish to do so. A series of studies have shown that providing the opportunity to plan usually exerts a positive impact on learners' productive skills (Foster & Skehan, 1996;Mehnert, 1998;Ortega, 1999;D'Ely, 2006;Guará-Tavares, 2008, 2011, 2013, with gains in performance even if the amount of planning time is minimal (Mehnert, 1998).…”
mentioning
confidence: 99%
“…The effects of planning on L2 performance can be analyzed in a number of respects (Mehnert, 1998) and through a number of tasks (Ortega, 1999) focusing on different facets of L2 planning such as task type and complexity (Foster, 1996;Foster & Skehan, 1996); the amount of planning time (Mehnert, 1998); planning processes (Ortega, 1999); planning for repetition (D'Ely, 2006); planning and working memory capacity (Guará-Tavares, 2011, 2013; online planning and self-repair behavior (Ahmadian, 2015); instruction on planning (Specht & D'Ely, 2017); individual versus collaborative planning (Zaccaron, 2018), to cite but a few examples. Despite the plethora of studies, more research is needed to better understand this complex issue.…”
mentioning
confidence: 99%